Performance Measurement of Robotic Process Automation in Policy Issuance Activities in Insurance Companies - M Ihza Mahendra Tampubolon; Irwan Bastian; Dewi Agushinta R (Diponegoro University, 2025)
The issuing policies process in the insurance industry is a complex activity that requires high precision, especially in verifying data and ensuring compliance with regulations. This process is often done manually, which takes a long time, is prone to errors, and is less efficient in handling high workloads. Robotic Process Automation (RPA) offers a solution to automate the policy issuance process to improve operational efficiency, reduce human errors, and speed up the process time. The research aims are to build RPA on the motor vehicle policy issuance process and measure its performance in comparison with the manual method. The research methods used include business process analysis, system design, RPA development using UiPath, testing, implementation, and performance evaluation based on five main variables: speed, availability, compliance, quality, and human resource efficiency measured by Full Time Equivalent (FTE). The results show that RPA can increase the efficiency of policy issuance by reducing processing time by 97.2%, from an average of 90 minutes per policy to 2 minutes 30 seconds. Regarding availability, RPA can operate 24/7 with an uptime of 99.9%. In addition, RPA result performance is 4,861 FTE in labor savings, ensuring compliance with regulations with a lower error rate than manual processes. However, certain cases still require manual intervention, especially in high-risk policies. The research results can serve as a reference for insurance companies in optimizing the implementation of RPA to enhance operational efficiency and provide faster and more accurate service to customers.